Mechanistic Insights into the Multiple Functions of Niacinamide: Therapeutic Implications and Cosmeceutical Applications in Functional Skincare Products - Cíntia Marques; Farid Hadjab; Alexandre Porcello; Kelly Lourenço; Corinne Scaletta; Philippe Abdel-Sayed; Nathalie Hirt-Burri; Lee Ann Applegate; Alexis Laurent (Antioxidants, 2024)
Niacinamide (or nicotinamide) is a small-molecule hydrosoluble vitamin with essential metabolic functions in mammalian cells. Niacinamide has become a key functional ingredient in diverse skincare products and cosmetics. This vitamin plays a pivotal role in NAD+ synthesis, notably contributing to redox reactions and energy production in cutaneous cells. Via diversified biochemical mechanisms, niacinamide is also known to influence human DNA repair and cellular stress responses. Based on decades of safe use in cosmetics, niacinamide recently gained widespread popularity as an active ingredient which aligns with the “Kligman standards” in skincare. From a therapeutic standpoint, the intrinsic properties of niacinamide may be applied to managing acne vulgaris, melasma, and psoriasis. From a cosmeceutical standpoint, niacinamide has been widely leveraged as a multipurpose antiaging ingredient. Therein, it was shown to significantly reduce cutaneous oxidative stress, inflammation, and pigmentation. Overall, through multimodal mechanisms, niacinamide may be considered to partially prevent and/or reverse several biophysical changes associated with skin aging. The present narrative review provides multifactorial insights into the mechanisms of niacinamide’s therapeutic and cosmeceutical functions. The ingredient’s evolving role in skincare was critically appraised, with a strong focus on the biochemical mechanisms at play. Finally, novel indications and potential applications of niacinamide in dermal fillers and alternative injectable formulations were prospectively explored.